Antibiotic induced changes to mitochondria result in potential contributions to carcinogenesis, heart pathologies, other medical conditions and ecosystem risks - Jyrkkanen, Jorma (Journal of Cardiology and Cardiovascular Medicine, 2020)
With the discovery by Calghatgi (2013) that three common antibiotics (Abs) increased mitochondrial reactive oxygen (ROS) and lipid peroxide (LP) and depleted their natural absorbant glutathione led me to investigate further the potential impacts of these genotoxic substances on carcinogenesis. The range of impacts on mitochondria and cellular DNA varied by antibiotic to those consistent with known prior contributions to carcinogenesis. Specific cancers probably increased by these changes were HCC, RCC (KCC), CRC, cancer of the esophagus. Tumor suppressor gene mutations resulting from LP were noteworthy in this regard and mutations induced in CRC were consistent with those found in carcinogenesis of CRC. In addition depression of short chain fatty acids in microbiomes were found which depress the immune system increasing risk of all cancers. Many cancers were increased according to epidemiological studies linking Abs with elevated odds ratios, with one concern in particular, fatal breast cancer. The impact of loss of functionality of the mitochondria was also linked to depression of the citric acid cycle and therefore ATP which deflected metabolism to glycolysis, the Warburg mechanism also increasing risk of all cancers, favoured by cancer cells. In conclusion, some portion of many cancer types are probably increased in likelihood by number, type and frequency of Abs treatment and chronic residue exposure which varies from individual to individual. This led me to propose a three pronged carcinogenesis mechanism for Abs. 1. Cancer critical mutations 2. Immune depression 3. loss of mitochondrial functionality leading to Warburg effects. Damage to mitochondria were also noted by common pesticides tested in China and cancer associations were also found for many pesticides supporting a similar contributory etiology. Heart health concerns were raised by these findings because of the myriad mitochondria in the heart and because of long term reliability needs. Studies suggesting hearts were affected by Abs and pesticide exposure were presented. Because of their geographical ubiquitousness and the huge range of diseases associated with mitochondrial dysfunction, antibiotics and pesticides and bacteriocidal biocides are of concern for biodiversity and life in general. I propose research steps to evaluate Abs safety and suggest directions for further research and make suggestions on ways to ameliorate Abs toxicity.